The Influence of Green Knowledge, Green Awareness and Green Packaging against the Purchase Decision of Aqua Life Drinking Bottle - Fazmi, Merlin; Imaningsih, Erna Sofriana (Journal of Sustainable Economic and Business, 2024)
Objectives: The objectives of this study is to test and analyze the effect of green knowledge, green awareness and green packaging on purchasing decisions for AQUA Life bottled drinking water (AMDK) products. Methodology: The data in the study is to obtain 100 respondents who had bought AQUA Life bottled water products domiciled in JABODETABEK. The research design used is using a combination of explanatory, descriptive and quantitative research. Sample measurement in this study using purposive sampling technique. Data analysis uses an alternative method of structural equation modeling (SEM), namely partial least square (PLS) and uses SmartPLS 4.0. The first stage in this study is to test the validity of the questions of each variable along with their reliability. The second stage examines the relationship between green knowledge, green awareness and green packaging on purchasing decisions for AQUA Life bottled water products. The results of this study state that all hypotheses are found to have a positive and significant effect. Finding: The current phenomenon that occurs is environmental pollution caused by plastic waste. Plastic waste is a major problem because it is difficult to decompose in the soil and takes a very long time. Conclusion: : The results of this study concluded that Green Knowledge has a positive and significant effect on Purchasing Decisions, Green Awareness has a positive and significant effect on Purchasing Decisions whereby Green Packaging also has a positive and significant effect on Purchasing Decisions.